Attention and Memory in Depersonalization-Spectrum Dissociative Disorders: Impact of Selective-Divided Attentional Condition, Stimulus Emotionality, and Stress. Issue 1 (1st January 2023) - Simeon, Daphne; Knutelska, Margaret; Putnam, Frank W.; Schmeidler, James; Smith, Lisa M.
ABSTRACT: We investigated cognition in depersonalization-spectrum dissociative disorders without comorbid posttraumatic stress disorder to explore evidence for emotionally avoidant information processing. Forty-eight participants with DSM-IV dissociative disorder (DD) (Depersonalization Disorder – 37, Dissociative Disorder NOS −11), 36 participants with Posttraumatic Stress Disorder (PTSD), and 56 healthy controls (HC) were administered the Weschler Adult Intelligence Scale-III (WAIS); the Weschler Memory Scale-III (WMS); and three Stroop tasks: the Standard Stroop, a selective-attention Emotional Stroop using neutral, dissociation, and trauma-related word categories, and a divided-attention Emotional Stroop using comparable words. Participants were also administered a paired-associates explicit and implicit memory test using emotionally neutral and negative words, before and after the Trier Social Stress Test. The DD and HC groups had comparable general intelligence and memory scores, though dissociation severity was inversely related to verbal comprehension and working memory. In the selective-attention condition, DD participants showed greater incidental recall across word categories with comparable interference. However in the divided-attention condition, DD participants significantly favored lesser attentional interference at the expense of remembering words. Across attentional conditions, DD participants had better recall for disorder-related than neutral words. Pre-stress, the DD group demonstrated better explicit memory for neutral versus negative words with reversal after stress, whereas the HC group demonstrated the opposite pattern; implicit memory did not differ. Cognition in the PTSD control group was generally dissimilar to the DD group. The findings in toto provide substantial evidence for emotionally avoidant information processing in DD, vulnerable to the impact of stress, at the level of both attention and memory.